Penerapan Metode Demonstrasi pada Pembelajaran IPA untuk Siswa Kelas IV UPTD SDN 017973 Kisaran Kota - Nur Wahyuni; Sri Darma Asmaniyah (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Science learning at school places greater emphasis on mastering basic scientific work abilities or science process skills, so that learning is more meaningful. However, based on observations made by researchers through field observations of the reality of science learning that takes place in class IV UPTD SD NEGERI 017973 KISARAN KOTA, it shows that there are still weaknesses in the science learning process which results in a decline in student learning outcomes. The weakness of science learning found in class IV UPTD SD NEGERI 017973 KISARAN KOTA is that this learning places more emphasis on mastering a number of facts and concepts, but does not facilitate students to obtain comprehensive and meaningful learning outcomes. The high percentage of students who have not been able to achieve the minimum completeness criteria, namely 36% indicated that the completeness of students' classical learning outcomes in this class was still not optimal so it needed to be improved. This research aims to improve the learning outcomes of class IV UPTD SD NEGERI 017973 KISARAN KOTA students by using the demonstration method in science learning.